Learning and teaching academic standards project : Health, Medicine and Veterinary Science : learning and teaching academic standards statement. - O'Keefe, Maree.; Henderson, Amanda; Pitt, Rachel (Australian Learning and Teaching Council, 2010)
The Learning and Teaching Academic Standards Statement for Health, Medicine and Veterinary Science is intended to offer a succinct description of the nature and extent of the discipline and to distinguish the threshold, ie minimum, level of achievement that can be expected of an Australian bachelor level graduate with a major in Health, Medicine and Veterinary Science. The Statement also sets out careers graduates might pursue.